Improving motivation in pre-school education through the use of project-based learning and cooperative learning - Viñuela, Yaiza; de Caso Fuertes, Ana María (Frontiers in Education, 2023)
The emphasis on skills-based learning has caused curricular change in education systems across the European Union, particularly in terms of the increased use of active teaching methodologies at all stages of education. These sorts of methodology are proven to have a positive impact on students’ motivation to learn and involve teaching strategies that represent a significant departure from traditional approaches. In this way, teachers in Pre-school Education can employ play-based strategies, which not only foster students’ acquisition of new skills but also their motivation. The objective of this study is to assess the impact of using active methodologies on the intrinsic motivation of students in the second cycle of Pre-school Education (3-6 years old) towards the process of teaching and learning. To this end, a quantitative investigation was undertaken involving a non-probabilistic, convenience sample of 77 students in publicly funded Pre-schools. The selected students were asked to complete an ad hoc questionnaire to measure their motivation with respect to the methodology implemented in their classroom. Data were analysed using the statistical programme SPSS v.26 statistical significance was reached for all motivation variables (p<0,05). A particularly important result was the finding that motivation among our pre-school cohort varied strongly in relation to sex with girls demonstrating greater motivation than boys. Also of interest are the findings that older pupils showed higher levels of motivation and students in the rural centre were more motivated than those who study in the urban centre. In conclusion, the implementation of active methodologies in Pre-school Education appears to foster students’ motivation to learn.